Analisis Sistem Pengendalian Internal Pada Pembiayaan Musyarakah di Pt. Bank Kb Bukopin Syariah Cabang Yogyakarta - Nurmalasari W; Ulinnuha Yudiansa Putra (AKUNTANSI 45, 2024)
Internal control plays an important role, serving as procedures and implementation guidelines for the operations of a particular company or organization. The correct implementation of internal control in a company will create a systematic work process and in accordance with organizational rules, so that a mutually supportive control environment will be created in every part of the company. This study aims to analyze how the implementation of the internal control system affects Musyarakah financing at PT Bank Bukopin Syariah Yogyakarta Branch. The research method used is descriptive qualitative method with data collection techniques using direct interviews with internal control system employees and business unit employees and direct observation at Bank Bukopin Syariah. The results of this study indicate that the implementation of the internal control system for financing with a Musyarakah contract at PT Bank Bukopin Syariah is in accordance with the applicable policy procedures in the company. Although the procedures for Musyarakah financing at PT Bank Syariah Bukopin Yogyakarta branch have functioned properly in accordance with applicable regulations or company standard operating procedures. Things are still found such as weak internal control in providing direction to customers during the process of disbursing financing with a large ceiling amount.